GENERAL I. APANASENKO'S CONTRIBUTION TO THE VICTORY IN THE SECOND WORLD WAR - N. Sudavtsov (Гуманитарные и юридические исследования)
The article deals with the commander of the Far Eastern Front, General I.R. Apanasenko, who made a signiicant contribution to the defense of the USSR in the Far East and ensuring victory in World War II. Being appointed commander of the front in January 1941, from the first days of his stay in the Far East, I.R. Apanasenko paid special attention to strengthening the defense capability of the region, increasing the combat readiness of troops to repel the enemy, which was very important during the Second World WWar. From the very first days of commanding the front, General I. Apanasenko paid great attention to the combat training of troops in conditions close to those of the front. The threat of a Japanese attack on the USSR increased signiicantly after the invasion of German troops into the territory of the Soviet Union on June 22, 1942. With the outbreak of World War II, troops had to be sent from the Far East to the west, while maintaining the combat readiness of the front. Sending out manned and fully secured military units, General Apanasenko took upon himself a huge responsibility, forming, on his own initiative, new divisions with the same numbers instead of departing ones. He made extensive use of misinformation, misleading the Japanese command, giving the appearance that regular military units continued to remain in place. The commander mobilized men up to 55 years old, removed prisoners from the camps and included them in the divisions being formed. As a result, the number of front troops not only did not decrease, but doubled. Not receiving weapons, ammunition, equipment, rations from the People's Commissariat of Defense and the General Staff, the front commander organized their production on the spot. The network of military state farms was expanded. The front became the base for the combat training of troops for the western fronts from among the conscripts sent from other territories to the Far Eastern Front. It was in 1941-1942 not only was the Japanese attack on the USSR prevented, but the foundations were laid for the preparation for military operations of the Soviet troops in the Far East in 1945.